Female’s sports injuries in selected team games - Pluta, Waldemar; Lubkowski, Michał; Huzarski, Oliwer (Journal of Education, Health and Sport, 2022)
Professional and recreational physical activity, is connected with a danger of injuries of locomotor system. Despite of a positive influence of physical motion on the human body, too much of workload makes the body exposed to rise up micro- and makrotrauma. Each sport discipline is characterized by its own rules and specificity of the game and training. Team games are distinguished by a large variable of factors influencing the athlete. The most traumatic sports disciplines are football and volleyball. The aim of the research was to evaluate and compare the injuries occurring in women training one of the above-mentioned disciplines. It has been shown that in both football and volleyball players, sprains of the ankle joint were the most common injuries in the lower limb, followed immediately by tears / ruptures of the knee ligaments. In the area of the upper limb, in footballers, a high percentage of shoulder contusions was noted, which may be related to the contact nature of the game. Volleyball players more often suffered injuries of the phalanges.